Multicenter phase II trial of nintedanib plus docetaxel in second-line treatment in advanced non-squamous non-small cell lung cancer patients refractory to first-line platin-based chemotherapy (REFRACT GFPC 02–15 study). (November 2021) - Auliac, Jean-Bernard; Monnet, Isabelle; Bizieux, Acya; Greillier, Laurent; Geier, Margaux; Falchero, Lionel; Le Garff, Gwenaelle; Lamy, Régine; Guisier, Florian; Ricordel, Charles; Chouaid, Christos; Vergnenegre, Alain; et al.
Highlights: The study included advanced non-squamous NSCLC refractory to 1st-line chemotherapy. Progression as best response during platin-based chemotherapy first line defined refractory state. Efficacy of nintedanib-docetaxel combination for 2nd-line treatment was assessed. One-year PFS was 11.8%; 12 and 18-months OS were 32.1% and 27.6% respectively. A subpopulation of these refractory patients seems to benefit from this combination. Abstract: Introduction: Advanced non-squamous non-small cell lung cancer (NsqNSCLC) progressing at the induction of a first-line of platin-based chemotherapy is a subgroup of patients with poor prognosis and few second-line treatment options. Materials and Methods: This single-stage phase II prospective multicenter open-label trial performed in platin-based refractory (i.e. progressing during induction phase of first-line platin-based chemotherapy) advanced NsqNSCLC assessed the efficacy of the nintedanib-docetaxel combination in second-line treatment. The primary endpoint was progression-free survival (PFS) rates at 12 weeks with a cut-off at 30% for ineffectiveness and 50% for minimal efficacy. Results: A total of 59 patients from 23 centers were included (mean age, 58.5 years; male gender, 73.6%; performance status 0–1, 100%; former/current smokers, 92.5%; adenocarcinoma, 92.5%, median platin-based first-line chemotherapy, 2). Nintedanib-docetaxel combination was administered for a median of 4 cycles. The rate of PFS at 12 weeks was 39.6% (95% CI, 28.2–56.8). Median PFS was 2.7 (95% CI, 1.4–4.1) months and one-year PFS was 11.8% (95% CI, 4.8–22.2). Median overall survival (OS) was 6.9 (95% CI, 4.3–8.2) months and 12-month OS was 32.1% (95% CI, 19.8–45.0); 18-month OS was 27.6% (95% CI, 16, 1–40.4). Twenty-nine (53.7%) patients reported at least one serious treatment-related adverse events leading to permanent discontinuation of at least one study drug in 12 (22.2%) patients. Conclusion: The predefined minimal efficacy was not demonstrated. However, a number of NsqNSCLC patients refractory to first-line platin-based chemotherapy appeared to benefit from this combination.